Criteria for Hardware Selection of Wireless Vibration Sensor - Akhondi, Mohammad Reza; Talevski, Alex; Chou, T. (Conference Publishing Services, 2010)
Vibration Sensor Hardware has three sub-fields as accelerometer, microcontroller and wireless device. This paper is dedicated to deliver more detail information on individual hardware and list of criteria for hardware selection in Wireless Vibration Sensors.